Attitudes and Beliefs About Brain Donation Among Black Americans. (20th December 2022) - Caban‐Holt, Allison M; Lloyd, Shawnta'; Starks, Takiyah D.; Ford, Tayla; Adams, Larry D.; Haines, Jonathan L.; Beecham, Gary W.; Beecham, Gary W.; Reitz, Christiane; Cuccaro, Michael L.; Vance, Jeffery M.; Pericak‐Vance, Margaret A.; et al.
Abstract: Background: African Americans (AA) are underrepresented in Alzheimer's disease (AD) brain donation research, making up approximately 2% of brain donations to the National Alzheimer's Coordinating Center (NACC). The objective of this study is to gain insights into the attitudes of Black∖AA individuals toward brain donation and perceptions of medical research that may hinder or facilitate brain donation. Method: A 35‐item survey was developed to understand the attitudes and beliefs about brain donation in a sample of AA, using survey items validated in prior investigations. Electronic and paper and pencil surveys were administered in Florida, New York and North Carolina, United States between November 2021‐January 2022. Descriptive analysis of demographic data and was conducted using SAS® software version 9.4. Result: The racial composition of the 135 respondents was primarily Black/African American (97.58%), with the remaining responses for race as "missing" or "prefer not to answer". Most respondents were women (73.6%). The majority of respondents report having a positive view about medical research (85.5%), while 72.1% believe that medical researchers can be trusted to protect the interests of participants. Many respondents reported wanting to learn more about AD (93.1%). Whereas, 82.0% report not knowing how researchers use a brain for research, 58.9% report knowing that study of the brain is important for advances in AD. Despite 53.1% of respondents reporting being either unlikely or unsure whether they would donate a loved one's brain even if that was their loved ones' wish, only 21.4% of the sample believe that the decision to donate one's brain is mostly a family decision. Overall, 63.8% of the respondents are either unsure or unlikely to donate their own brain. Conclusion: Findings suggest that 1) awareness of brain donation research procedures and processes should be focused on whole family education, and 2) increasing knowledge about AD will be fruitful areas for an educational intervention. Including families in the consenting processes will be pivotal in ensuring that brain donation occurs. Results will be utilized to develop a community‐informed educational program for Black communities about AD research and brain donation.